Expression and significance of HMGB1 in patients with sepsis and effects on prognosis. Issue 1 (1st January 2020) - Xin, Keke; Sun, Junli; Liu, Ping; Ge, Jianlin; Leng, Chenghui; Pang, Feng
Abstract : This study explored the expression of high mobility group box 1 protein (HMGB1) expression in patients with sepsis and its effects on immune function and prognosis. Patients with sepsis ( n  = 112) were divided into the mild group (MG, n  = 59) and severe group (SG, n  = 53) according to the disease severity of sepsis. Fifty healthy people who came to our hospital for physical examination at the same time served as the control group (CG). Serum HMGB1, CD4+, and CD8+ expression levels and CD4+/CD8+ ratios were compared between the three groups. The correlation between serum HMGB1 expression, APACHE II score, and MODS score was analyzed. Serum HMGB1 and CD8+ expressions were lower in the CG group than the values in the MG and SG groups, whereas the CD4+ expression and CD4+/CD8+ ratio were higher. Serum HMGB1 expression in sepsis patients was positively correlated with the APACHEII and MODS scores. In addition, the 28-day survival rate of the MG was higher than that of the SG. HMGB1 was highly expressed in the serum of patients with sepsis. HMGB1 expression was positively associated with the severity of sepsis. In addition, HMGB1 was closely related to the immune function and prognosis of patients with sepsis.